Sistem Keamanan Parkir Roda Dua Menggunakan Radio Frequency and Identification (RFID) - Andre maulana; Dani Sasmoko; Iman Saufik Suasana (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2020)
Security Parking UIN Walisongo Semarang at this time can be said to be in poor condition. The high case of loss of a motor vehicle cause anxiety for the academic community. Parking system that is traditional that is doing the checking of identity cards at the exit of the campus is less effective. Hence the need for a system of security parking modern and computerized, so that activities out of the vehicle can be recorded and stored automatically. Based on these problems, the authors designed a parking Security System as a WEB-based form of increased security parking campus UIN Walisongo Semarang. By using RFID technology (Radio Frequency Identification) are planted on the card identity, which can later be used as an authentication tool typing will enter and exit the campus area. To provide double security, there are Features of the Live Camera with the base website that serves as a tool for monitoring vehicles that are parked in real time. The output of this final project is to produce a prototype security system parking. Not only specialized hardware, but also software design of the System monitoring of vehicles in live Web-based. So the users of the parking facilities can monitor the vehicle anywhere.